A delocalizable cationic headgroup together with an oligo-oxyethylene spacer in gemini cationic lipids improves their biological activity as vectors of plasmid DNA1. Issue 8 (28th February 2015) - Kumar, Krishan; Barrán-Berdón, Ana L.; Datta, Sougata; Muñoz-Úbeda, Mónica; Aicart-Ramos, Clara; Kondaiah, Paturu; Junquera, Elena; Bhattacharya, Santanu; Aicart, Emilio
<x xml:space="preserve">Abstract</x> Lipoplexes of plasmid DNA and mixed liposomes, with a gemini cationic lipid of the 1, 2-bis(hexadecyl imidazolium) oxyethylene series, improves their biological activity.